About brownian movement in liquids - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It has been shown that Brownian movement in water occurs as a result of elastic collisions of ice nanocrystals with Brownian particles. Water consists of 87 % of ice nanocrystals and 13 % of water molecules. At 300 K, the ice nanocrystal in water on average consists of 24 water molecules. Brownian movement is an experimental confirmation of the nanocrystalline structure of liquids. This concept of liquids is of great importance for the theory of crystallization and modification of alloys. In metallic liquids, Brownian motion refers to microscopic non-metallic particles and intermetallides that have densities comparable to melt densities. In liquid aluminum alloys, Brownian particles are microscopic alumina particles that remain in the castings when they solidify.